2019
DOI: 10.3389/fvets.2019.00114
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Bacitracin Methylene Disalicylate (BMD) on the Distal Colon and Cecal Microbiota of Young Broiler Chickens

Abstract: Antibiotics have been used extensively for growth promotion in poultry, along with other food production animals, as well as therapeutically to treat infectious diseases. However, with concerns over selection for drug antibiotic resistant bacteria the practice of using subtherapeutic doses of antibiotics is under increased scrutiny. Consequently, we assessed the impact of the commonly used antibiotic bacitracin methylene disalicylate (BMD) on the gastrointestinal microbiota of chickens. For this we administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 61 publications
(60 reference statements)
4
38
0
Order By: Relevance
“…Lower ileal and cecal LAB counts have been reported in BMD-added broilers compared to those fed diets without BMD [36,45,46]. In agreement with our results, broilers reared in floor pens and added with HS showed increased LAB counts in the digesta collected from the distal end of the duodenum to the ileocecal junction and cecum compared to those fed a diet added with flavomycin [47].…”
Section: Effect Of Dietary Treatmentssupporting
confidence: 91%
See 1 more Smart Citation
“…Lower ileal and cecal LAB counts have been reported in BMD-added broilers compared to those fed diets without BMD [36,45,46]. In agreement with our results, broilers reared in floor pens and added with HS showed increased LAB counts in the digesta collected from the distal end of the duodenum to the ileocecal junction and cecum compared to those fed a diet added with flavomycin [47].…”
Section: Effect Of Dietary Treatmentssupporting
confidence: 91%
“…It seems that in the positive control and EHS-fed broilers, the amount of nutrients used for the synthesis and storage of meat was similar, but this amount was lower in the negative control broilers, which led to lower carcass yield. It is probably that in negative control broilers higher amounts of nutrients were diverted to strengthen the immune response due to the removing of GPA from the feed that may increase the risk of bacterial challenges in the gut [3,36]. Nevertheless, the authors were aware that there was no a clear explanation of these results and the topic requires further clarification.…”
Section: Effect Of Dietary Treatmentsmentioning
confidence: 99%
“…In agreement with the present study, Tang et al 7 and Ohh et al 38 reported that AMPs significantly enhanced the microflora balance in the ileum of piglets and broilers, respectively. The antimicrobial action of Bacitracin Methylene Disalicylate (BMD) involves blocking the bacterial ribosome subunits and subsequently impeding protein synthesis, which finally reduces the colonization of the microbial community in the intestine 39 . Unfortunately, this antibiotic does not differentiate between commensal vs. pathogenic bacteria and may perturb microbial balance in the intestine and deprive the host of benefits of microbes’ roles and products 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the present study, Tang et al [7] and Ohh et al [38] reported that AMPs significantly enhanced the population of beneficial bacteria and decreased the colonization of harmful ones in the ileum of piglets and broilers, respectively. The antimicrobial action of Bacitracin Methylene Disalicylate (BMD) involves blocking the bacterial ribosome subunits and subsequently impeding protein synthesis, which finally reduces the colonization of microbial community in the intestine [39]. Unfortunately, this antibiotic does not differentiate between beneficial vs. pathogenic bacteria and may perturb microbial balance in the intestine and deprive the host of benefits of microbes’ roles and products [40, 39].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial action of Bacitracin Methylene Disalicylate (BMD) involves blocking the bacterial ribosome subunits and subsequently impeding protein synthesis, which finally reduces the colonization of microbial community in the intestine [39]. Unfortunately, this antibiotic does not differentiate between beneficial vs. pathogenic bacteria and may perturb microbial balance in the intestine and deprive the host of benefits of microbes’ roles and products [40, 39]. There is no consensus on the mechanism by which AMPs influence bacterial colonization in the intestine, while two direct and indirect mechanisms have been proposed based on the physiological properties of peptides.…”
Section: Discussionmentioning
confidence: 99%